2011
DOI: 10.2165/11531500-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Economic Burden of Osteoporosis in New Zealand

Abstract: Osteoporosis and osteoporotic fractures create a significant burden on the health system in New Zealand. This study highlights the significant scope of the burden of osteoporosis and the potential gains that might be made from introducing interventions to mitigate the burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Although the majority of burden of illness studies only reported the costs associated with osteoporosis-related hospitalizations [32, 3436], non-acute care accounted for almost 50% of our base case direct cost estimates, which was higher than estimates reported in the US (38%) [37], Germany (33%) [30], and New Zealand (33%) [31]. Differences in the cost categories included in the non-acute care calculations may explain these variations (e.g., home care and long-term care).…”
Section: Discussionmentioning
confidence: 92%
“…Although the majority of burden of illness studies only reported the costs associated with osteoporosis-related hospitalizations [32, 3436], non-acute care accounted for almost 50% of our base case direct cost estimates, which was higher than estimates reported in the US (38%) [37], Germany (33%) [30], and New Zealand (33%) [31]. Differences in the cost categories included in the non-acute care calculations may explain these variations (e.g., home care and long-term care).…”
Section: Discussionmentioning
confidence: 92%
“…When investigating, e.g. hip fractures, other studies have shown results within the range of EUR 15,500–50,000 when converted to 2011 prices by consumer price index (for European countries, harmonized indices of consumer prices in health care have been used) [6, 14, 15, 41, 42]. This study showed that the estimated cost of hip fractures was EUR 13,683 for men and EUR 9,385 for women, which also included productivity cost.…”
Section: Discussionmentioning
confidence: 99%
“…The complete societal burden of osteoporotic fractures should therefore also include quality of life, as this is an important aspect of patients' well-being. COI studies from Sweden [6, 9], New Zealand [41] and Germany [43] show that osteoporosis and osteoporotic fractures impose a significant loss in quality of life. Thus, it must be expected that similar findings would be found for the Danish population.…”
Section: Discussionmentioning
confidence: 99%
“…It is a global problem seen most often in the elderly and in women (80%) [1] and is considered one of the ten most important diseases affecting the world’s population [2] and is particularly prevalent in developed countries with ageing populations and longer life spans [3]. Bone loss is accelerated at early menopause resulting in increasingly fragile bones prone to breakage.…”
Section: Introductionmentioning
confidence: 99%
“…The number of older (> 50 years) New Zealanders is increasing steadily and the cost of treating fractures and secondary illnesses related to osteoporosis is expected to rise from $330 million in 2007 to $458 million by 2020 [3]. …”
Section: Introductionmentioning
confidence: 99%